Mortality of Japanese Olympic athletes in 1964 Tokyo Olympic Games. Issue 1 (18th January 2021) - Takeuchi, Taro; Kitamura, Yuri; Ishizuka, Soya; Yamada, Sachiko; Aono, Hiroshi; Kawahara, Takashi; Sobue, Tomotaka
Abstract : Objectives: To compare the mortality of Japanese athletes in the 1964 Tokyo Olympic Games with that of the Japanese population, and to elucidate factors associated with their mortality. Methods: We obtained from the Japan Sport Association study subjects' biographical information, information on lifestyles and medical data. Missing data were obtained from online databases. Standardised mortality ratio (SMR) was calculated to compare athletes' mortality with the Japanese population. Cox proportional hazards model was applied to estimate the HR for each category of body mass index (BMI), smoking history and handgrip strength. This analysis was limited to male athletes due to the small number of female athletes. Results: Among 342 (283 men, 59 women) athletes, deaths were confirmed for 70 (64 men, 6 women) athletes between September 1964 and December 2017. Total person years was 15 974.8, and the SMR was 0.64 (95% CI 0.50 to 0.81). Multivariate analysis performed on 181 male athletes. Mortality was significantly higher for BMI≥25 kg/m 2 than for 21–23 kg/m 2 (HR: 3.03, 95% CI 1.01 to 9.07). We found no statistically significant associations between smoking history and mortality; the HR (95% CI) for occasional and daily smokers were 0.82 (0.26 to 2.57) and 1.30 (0.55 to 3.03) compared with never smokers. We also found no statistically significant associations between handgrip strength and mortality (P for trend: 0.51). Conclusion: Japanese athletes in the 1964 Tokyo Olympic Games lived longer than the Japanese population. BMI≥25 kg/m 2 was associated with higher mortality, but smoking history and handgrip strength were not associated with mortality.